How to read Derrida - Deutscher, Penelope, 1966- (London : Granta Books, 2005)
An idiosyncratic and controversial French philosopher, Jacques Derrida inspired change in many disciplines, including law, literature and anthropology. This text makes approaching Derrida's work less fearsome and gives helpful advice on how to interpret his writings.
Deconstructive reading -- Reading as intervention -- Differance -- Undecidables -- Culture, gender, and politics -- The context of communication -- Mourning and hospitality -- Giving and forgiving -- Justice and the law -- Perfectibility.
Includes bibliographical references and index.
Keywords: Derrida, Jacques -- Criticism and interpretation